Education model on SMS gateway on blood sugar levels of diabetes mellitus patients - Febriyanti, Febriyanti; Yusri, Viki; Guci, Asriwan (University of Muhammadiyah Malang, 2023)
Introduction: Diabetes has become a global epidemic over the last two decades, the prevalence has doubled, from 4.6% to 9.3% in the population aged 20-79 years. Based on data from the International Diabetes Federation (IDF) 2019, it is estimated that 463 million people in the above age group live with diabetes of which 90% Diabetes, Indonesia faces the same diabetes threat as the world, within five years. West Sumatra is at number 21 out of 34 provinces with diabetes cases. Based on data from the Padang City Health Office in 2020, from 23 health centers in Padang City, Andalas Health Center is the highest coverage of type 2 diabetes mellitus, which is 1017 people. Of the 10 sub-districts in the Andalas Community Health Center working area, Jati sub-district is the highest case of diabetes mellitus. Good blood sugar control is one of the important factors and has been shown to reduce the risk of complications in people with diabetes, to achieve good blood glucose control, holistic management is needed including education, education with an SMS gateway approach can provide continuous and continuous information. Objectives: see the effect of SMS gateway-based education model on blood sugar levels of diabetics. Methods: Pre-experiment using the One Group Pretest-Posttest design approach. Data analysis using Paired T-test sample. Results: The results showed that there was an effect of education model based on sms gateway based education model on blood sugar levels of diabetics with p-value = 0.002. Conclusions: SMS gateway-based education model affects blood sugar levels of diabetics.